2009
DOI: 10.1007/s13312-010-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent short course therapy for pediatric tuberculosis

Abstract: We conducted this study to assess the efficacy of intermittent short course therapy in all forms of pediatric tuberculosis using a coordinated approach with Revised National Tuberculosis Control Programme (RNTCP). Sixty five children were treated using RNTCP protocols with some modifications, such as dose adjustments or prolongation of treatment in selected children. Overall response rate was 95%(pulmonary 94% and extra pulmonary 97%). There was one case with possible relapse. With dynamic inputs from both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
2
7
1
Order By: Relevance
“…The treatment outcome in paediatric TB is gauged according to the clinical parameters which are different than the adult counterparts. Most of the patients were female similar to studies done by Sharma S et al, 8 C K Indumathi et al 9 The high prevalence of cases in females in our study could be explained by the fact that most of our study population belonged to lower socioeconomic class where the females exposed to the infection are more prone to develop the disease due to either poor nutritional status or poor immunity. The poor BCG vaccination status in females might also be a responsible factor for acquiring the infection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The treatment outcome in paediatric TB is gauged according to the clinical parameters which are different than the adult counterparts. Most of the patients were female similar to studies done by Sharma S et al, 8 C K Indumathi et al 9 The high prevalence of cases in females in our study could be explained by the fact that most of our study population belonged to lower socioeconomic class where the females exposed to the infection are more prone to develop the disease due to either poor nutritional status or poor immunity. The poor BCG vaccination status in females might also be a responsible factor for acquiring the infection.…”
Section: Discussionsupporting
confidence: 89%
“…(Table 1). In the present study, mean age of presentation (6.9 years, SD = 3.7) is younger than other studies in tertiary care institutes (CK Indumathi et al, 9 Shivanandan S et al, 10 Shrestha S et al 11 ), may be because of more number of malnourished children in this study who might have presented earlier in the disease process. The nutrition has significant impact on the outcome of TB.…”
Section: Discussioncontrasting
confidence: 65%
“…In other studies, the completion/ cure rates varied from 80% to 94.9% as shown in Table 2. 4,7,15,16 Higher treatment completion rates in the present study was due to strict adherence to DOTS strategy under RNTCP, the medicines were available without break and good compliance of the patients. There were no adverse effects due to anti-tubercular drugs in the present study.…”
Section: Discussionmentioning
confidence: 70%
“…[6][7][8] Only 30 cases (33%) belonged to the below 5 years age group. Other studies have reported maximum number of patients in 1-5 years age group.…”
Section: Discussionmentioning
confidence: 99%
“…No relapse occurred in the patients who received 6-month intermittent therapy, although there were four relapses in the 9-month group. (20). The overall cure rate was 95%, and radiological response was noted in 90% of children.…”
mentioning
confidence: 89%